PERSEPSI GURU TERHADAP SURAT EDARAN KEMENDIKBUD NOMOR 14 TAHUN 2019 TENTANG PENYEDERHANAAN RPP DI SMA NEGERI SE KECAMATAN XIII KOTO KAMPAR - Ninda Usria; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is a problem which appear in making and forming lesson plan. The formulation of this problem is how Teachers Perception on Kemendikbud Form Letter Number 14 in 2019 About Lesson Plan Simplification in Sub-District XII Koto Kampar Senior High School and how the lesson plan implementation in performing sub-district XII Koto Kampar senior high school learning. The aim of this research is to know teachers perception on Kemendikbud form letter number 14 in 2019 about lesson plan simplification and to know the lesson plan implementation in performing sub-district XII Koto Kampar senior high school learning. The advantages of this research are enhancing knowledge, insight and understanding as to teachers’ perception on Kemendikbud form letter number 14 in 2019 about lesson plan simplification, sources and as consideration for all parties especially teachers in educational world for education quality. The analytical technique which is using in this research is quantitative descriptive, questionnaires for the data collection instrument which contains of 21 questions with 6 indicators and total sampling as the research sample. The population of this research is sub-district XII Koto Kampar senior high schools’ teachers. This research has been concluded by looking for the result which is teachers’ perception on Kemendikbud form letter number 14 in 2019 about lesson plan simplification in place “SangatBaik”. Responders who answered “SangatSetuju” with total 63.58% adding up with the result of responders who answered “Setuju” with total 32.66% is 96.24%. This range placed in category “Sangat Baik” with range 75.01% - 100%. The result of teachers’ perception on Kemendikbud form letter number 14 in 2019 about lesson plan simplificationsub-district XII Koto Kampar senior high school occurred in range “SangatBaik”.Kata Kunci: Teachers’ Perception, Form Letter Number 14 in 2019